Experimental Investigation of the Effect of Steam Dilution on the Combustion of Methane for Humidified Micro Gas Turbine Applications. Issue 8 (2nd August 2016) - De Paepe, Ward; Sayad, Parisa; Bram, Svend; Klingmann, Jens; Contino, Francesco
ABSTRACT: Water introduction in the micro gas turbine (mGT) cycle is considered the optimal route for waste heat recovery and flexibility increase of such a small-scale combined heat and power (CHP) unit. However, humidification of the combustion air in a mGT affects combustion stability, efficiency, and exhaust gas emissions. This can lead to a non-stable, incomplete combustion, which will affect the global efficiency negatively. Additionally, CO emissions will increase. The non-stable, incomplete combustion might result in an engine shutdown due to a flameout. To study the impact of humidification on the combustion of methane in a humidified mGT, we performed combustion experiments in an atmospheric, variable-swirl, premixed combustion chamber. The results of these experiments are summarized in this article. The effect of the humidification of the combustion air was simulated by adding steam to the combustion air. The impact of the steam injection on methane combustion has been studied at variable swirl number and steam fraction. Experimental results showed a linearly increasing lean blowout (LBO) equivalence ratio for methane combustion with increasing steam fraction. In addition, CO emission levels started to rise at higher equivalence ratio for higher steam fractions compared to combustion under dry conditions. The CO emission levels at stable combustion were however still the same order of magnitude as for the dry combustion. The swirl number has little effect on the LBO limit. Final results indicated the possibility to maintain complete and stable combustion under humidified conditions with low CO emissions at higher equivalence ratio compared to the dry combustion.